Efficacy of Kinesio Tapping vs Mulligan Tapping in Reducing Pain and Improving Hamstring Flexibility, Cadence, and Physical Performance in Individuals with Patellofemoral Pain Syndrome - Zainab Tariq, Syeda Aiman Batool, Amaar Talib, Nabeel Amjad, Iqra, Maryam Asghar Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Pain in the kneecap (patellofemoral joint) or the surrounding soft tissues (ligaments, tendons, etc.) might be grouped together under the umbrella term patellofemoral pain syndrome. Squatting, sit-to-stand exercise, stair climbing activity, jogging, and running are all associated with a worsening of patellofemoral pain syndrome, a chronic disease (2). Objective and Methodology: The purpose of this study is to evaluate the efficacy of kinesio tapping vs Mulligan tapping in reducing pain and improving hamstring flexibility, cadence, and physical performance in individuals with patellofemoral pain syndrome. It was a randomized control experimental trial study with total 20 participants randomly allocated into group A (kinesio taping) and group B (Mulligan tapping). Outcomes included were pain, cadence, physical performance of lower limb and hamstring flexibility. Outcomes were assessed and compared at baseline, after 24 hour, after 48 hour and after 72 hours of tapping application. Data was analyzed with SPSS 21, Shapiro-wilk test for calculating the normality+ of data and two-way mixed ANOVA was applied for outcome comparison. Results: In all, the sample had a mean age of 26.85 + 3.63 years. The average age of those in Group A was 26. + 3.47 years, while those in Group B were 27. + 3.78 years. There were 60% women and 40% men in group A, and 30% men and 70% women in group B. After the treatment period ended, all outcome variables had improved significantly in both groups (P0.05), and there was no significant group difference except for cadence scores (F (3, 54) = 8.039, P = 0.007, 2 = 0.309). Conclusion: The study concluded that Kinesio tapping and Mulligan tapping both are effective in improving cadence, hamstring flexibility, lowering pain, patellofemoral pain severity and physical performance. Keywords: Anterior knee pain, Hamstring, Knee pain, Kinesio tapping, Pain, Patellofemoral pain, Tapping.